Penggunaan Instagram sebagai Media Promosi Taman Baca Melego Cimanggis - Alfharezi, M. Salman (Media Pustakawan, 2025)
The development of information and communication technology has encouraged the use of social media as a promotional tool, including for community reading centers. Instagram, as one of the most popular platforms, enables these centers to reach a wider audience, raise literacy awareness, and build digital communities. This study analyzes the use of Instagram as a promotional medium for Taman Baca Melego in Cimanggis, Depok. A quantitative approach was used, focusing on measuring the engagement rate of followers with content published on the Instagram account @tamanbacamelego. Data were collected from 247 posts published between 10 December 2019 and 3 November 2024, and compiled as of 25 January 2025. Likes, comments, and shares were used as the main indicators of interaction. The results indicate that @tamanbacamelego maintained a stable engagement rate of approximately 2.95%, suggesting the effectiveness of social media strategy in fostering audience interaction. However, to expand its reach, the account needs to optimize more interactive content and implement additional digital campaigns. It is expected to adopt strategies that improve engagement and strengthen its role as an effective digital literacy platform. Ongoing content innovation and adaptation to social media trends are also essential for sustaining long-term follower engagement.